Acartia (Acanthacartia) lishaojingi sp. nov. (Copepoda, Calanoida) from Xiamen, southeastern China - Gong, Zhidi; Guo, Donghui (Zootaxa, 2025)
A new species, Acartia (Acanthacartia) lishaojingi sp. nov., is described based on specimens collected from the Longzhou Pool, Xiamen, China. Morphologically, this new species should be assigned to the A. plumosa group, characterized by a basal knob-like swelling on exopod of female leg 5, a thumb-like projection on the basis as well as a long terminal segment and a short terminal spine on male left leg 5. Among the A. plumosa group, A. lishaojingi sp. nov. most closely resembles A. sinjiensis. Phylogenetic analyses based on mitochondrial gene cytochrome oxidase subunit I (mtCOI) sequences showed that the inter-specific genetic differences between A. lishaojingi sp. nov. and A. sinjiensis ranged from 20.9–21.3%, demonstrating that the new species is distinct from A. sinjiensis. A. lishaojingi sp. nov. can be differentiated from A. sinjiensis by combination of the following characteristics: in the female, posterior corners of fifth pedigerous somite typically naked; second urosomite with only two spinules on posterodorsal margin; posterodorsal spinules on genital double-somite smaller than those on second urosomite; in the male, third urosomite without spinules on posterodorsal margin; basis of left leg 5 with distally-narrowed thumb-like projection and without acute projection on medial margin.